Analysis of Indonesia’s Primary Weapon Systems Modernization Policy as a Geopolitical Strategy in Southeast Asia, 2020–2025 - Yasmin, Muhammad Al Fajar; Prayuda, Rendi; Sary, Dian Venita (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2026)
The geopolitical dynamics of Southeast Asia during the 2020–2025 period have been shaped by intensifying great power rivalry, rising tensions in the South China Sea, and the transformation of security threats toward multidimensional forms, positioning the modernization of Indonesia’s main weapon systems (alutsista) as a critical instrument for strengthening national defense while reinforcing the country’s geopolitical posture. This study analyzes Indonesia’s defense modernization policy as a geopolitical strategy and identifies structural constraints affecting its implementation through a qualitative descriptive policy analysis based on literature review and secondary data from defense policy documents, government reports, and international security publications, grounded in realist theory and foreign policy analysis that emphasize the state’s role within an anarchic system characterized by power competition and security dilemmas. The findings indicate that modernization performs a dual defense–geopolitical function by enhancing military readiness, supporting Minimum Essential Force (MEF) targets, strengthening deterrence, maintaining regional balance of power, and elevating Indonesia’s strategic bargaining position; however, its effectiveness remains constrained by limited defense budgets, technological dependence on foreign suppliers, underdeveloped domestic defense industry capacity, and inconsistent long-term strategic planning. The study also evaluates modernization through indicators of deterrence posture, strategic signaling, and defense industrial autonomy to measure its geopolitical effectiveness beyond material capability enhancement. The study concludes that the success of defense modernization as a geopolitical strategy depends on the integrated alignment of defense policy, defense diplomacy, and national defense industrial development to achieve sustainable strategic autonomy and reinforce regional stability amid intensifying geopolitical competition